Joint Pain with Activity of Daily Living (ADL) Levels in Elderly People in Sempalwadak Village, Bululawang Community Health Center Working Area - Sisilia Dwi Agustina; Ellia Ariesti; Yustina Emi Setyobudi; Febrina Secsaria Handini (Poltekkes Kemenkes Aceh, 2025)
Background: Elderly individuals are individuals entering the final stages of human development. As they age, they experience functional decline, particularly in the musculoskeletal system, leading to conditions such as osteoarthritis, rheumatoid arthritis, and gout, which can cause joint pain. Frequent, persistent joint pain can lead to a decline in daily living activities. Purpose: To determine the relationship between joint pain and the level of Activity of Daily Living (ADL) ability in the elderly in Sempalwadak Village, Bululawang Health Center working area. Methods: This study used a quantitative correlational design with a cross-sectional approach. The study population was all elderly residents of Sempalwadak Village who were patients at the Bululawang Community Health Center. The sampling technique was total sampling, with a total sample size of 70 elderly residents. The instruments used included the Numeric Rating Scale (NRS) pain scale and the Activity of Daily Living (ADL) form using the Bathel Index, which consists of ten activities. Data analysis used the Spearman rank test. Results: Based on the Spearman rank test, the p value was obtained = 0.00 (<0.05), which means there is a relationship between joint pain and the level of Activity of Daily Living (ADL) ability in the elderly in Sempalwadak Village, Bululawang Community Health Center working area. Conclusion: Joint pain is significantly associated with functional independence in carrying out daily activities in older adults. Pain management should be prioritized to maintain ADL capacity in older adults.